A study of correlation of different grades of malnutrition with feeding practices during 1st 6 months of life - Sharma, Diksha; Sareen, Devendra; Bamnawat, Subhash (International Journal of Contemporary Pediatrics, 2017)
Background: Childhood under nutrition is a critical public health and development challenge in many developing countries including India. Nearly half of all deaths in children under-5 age group are attributable to under-nutrition. One of the key reasons for under-nutrition in early life is the faulty and sub-optimal infant and young child feeding practices. Methods: 295 children under the age of 5 years residing in rural areas of Udaipur were studied. Feeding pattern and various demographic factors were taken into account, considering age at which breastfeeding was initiated, practice of exclusive breastfeeding up to 6 months, colostrum given or not, any pre-lacteal feed given or not. Assessment of anthropometric measurements was done and children were categorized as per classification of malnutrition by the WHO. Results: Total of 295 children were studied, out of which 59% (174) children were malnourished. 23.2% of SAM children received exclusive breastfeeding up to 6 months compared to 52.1% of control group, which was statistically significant. Difference between severely malnourished and control group children who received pre-lacteal feed was also significant. Only 21% of severely malnourished children were started with breastfeeding within 1st hour of birth. Conclusions: Most of the children who were not given breastfeeding up to 6 months, offered pre-lacteal feed, deprived of colostrum at birth, not started complementary feeding at appropriate time were severely malnourished.